Prehospital methods applied in migraine attack Prehospital migraine attack - Goktekin, Mehmet Cagri (Bayrakol Medical Publisher, 2019)
Aim: In this study, we aimed to detect the pharmacological and nonpharmacological methods used by the migraine patients before applying to the emergency department, and the factors triggering the migraine attack. Material and Method: Patients accepted to the emergency department due to a migraine headache were included in the study. Patients who had repetitive applications and those who did not approve participating in the study were excluded from the study. Their demographic features, possible triggering factors and what they do to eliminate a headache before applying to the emergency department were recorded. Results: The average ages of male and female patients were 33.7 +/- 10,6; 71,4% (n=200) of the patients were female. The menstruation was detected as one of the primary triggering factors in 28% (n=56) of the female patients. The other triggering factors for all patients were stress (83,6%), sleeplessness (72,1%), starvation (55,7%), malodor (44,3%), gurgling (25,4%), nutrient (20%), more light (19,3%), extreme cold weather (18,6%), fatigue (13,9%), extreme hot weather (10%), and smoking (7,5%). The methods that the patients used for a headache relief before applying to the emergency department were following: drugs intake (62,9%), nutrients intake (47,1%), massage (45%), exercises (34,3%), trying to sleep (32,1%), going out for fresh air (25,4%), and taking a shower (21,8%). Discussion: Although the ordinary analgesia or non-pharmacological methods are used by many patients when a migraine attack happens, the headaches do not sufficiently relieve and they apply to the emergency departments.
Keywords: Migraine; Triggering Factors; Prehospital